Study of Energy and Structure on Interactions Between Molecules In Solvents - Organic Solves Using Computational Chemical Methods - Nur Aisah Malau; Asep Wahyu Nugraha (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
This study aims to determine the amount of energy, the difference in energy, the relationship between the amount of energy and the distance between compounds, and the interactions that occur in organic solvent molecules using computational chemistry methods. In determining the amount of energy and interactions that occur, computational chemistry calculations are used using NWChem software version 6.6 with the DFT method with the B3LYP hybrid function/basis set 6-31G, the calculation results are visualized using Jmol software. The results of calculations with large computations of energy for benzene are -230.62447487 KJ/mol, ethanol -154.01322923 KJ/mol, methanol -114.98816558 KJ/mol, hexane are -235.27001385 KJ/mol. Mixture of benzene and ethanol in a ratio of 1 : 1 -384.63823964 KJ/mol, 1 : 2 538.66009762 KJ/mol , and 2 : 1 -615.26607558 KJ/mol. A mixture of benzene and methanol in a ratio of 1 : 1 -345.61255299 KJ/mol, 1 : 2 -460.60826254 KJ/mol, and 2 : 1 -576.24044425 KJ/mol, a mixture of hexane and ethanol in a ratio of 1 : 1 -389.28477268 KJ/mol, 1 : 2 -543.29869234 KJ/mol and 2 : 1 -624.55723290 KJ/mol. A mixture of hexane and methanol at a ratio of 1 : 1  -350.25984691 KJ/mol, 1 : 2 -465.26041654 KJ/mol and 2 : 1 -585.53373886 KJ/mole. The difference in energy is the most in a mixture of benzene and ethanol in a ratio of 1 : 2 -0.00916429 K /mol, in a mixture of benzene and methanol in a ratio of 1 : 2 - 0.00745651 KJ/mol, a mixture of hexane and ethanol in a ratio of 2 : 1 -0.00397597 KJ/mol, and a mixture of hexane and methanol in a ratio of 1 : 2 -0.01407153 KJ/mol. and there is no relationship between the magnitude of the interaction energy of the mixture with the distance between the molecules.